1962
DOI: 10.1021/jo01051a031
|View full text |Cite
|
Sign up to set email alerts
|

The Alkali Salts of 2,2-Diphenyl-1-picrylhydrazine1

Abstract: Hoboken, N. J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As a result, the two ortho nitro groups are rotated through large angles to avoid close contacts between nitro oxygen atoms and N(4). In particular, the nitro groups analogous to O(1)-N(1)-O (2) in the ion are rotated 60.6 and 57. l o from coplanarity with the trinitrobenzenide ring in the two independent molecules of the free radical. The boat conformation in the ion obviates the need for much of this rotation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the two ortho nitro groups are rotated through large angles to avoid close contacts between nitro oxygen atoms and N(4). In particular, the nitro groups analogous to O(1)-N(1)-O (2) in the ion are rotated 60.6 and 57. l o from coplanarity with the trinitrobenzenide ring in the two independent molecules of the free radical. The boat conformation in the ion obviates the need for much of this rotation.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation and characterization of salts produced by the reaction was reported by Weil and Janusonis (2) in 1962. Their nmr results indicated that the 1-(N,Ndipheny1hydrazono)-2,4,6-trinitrobenzenide ion was indeed formed.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Preliminary investigation revealed that the intensity of the characteristic absorption band of DPPH (1a) at λ max = 520 nm decreases due both to the formation of the anion (3a) with λ max = 428 nm [8,38] via a redox process involving the superoxide radical-anion (eqs. 4 and 5), and to other reactions.…”
Section: Reaction With Potassium Superoxide In the Presence Of Crown mentioning
confidence: 99%
“…The main constituents of the reaction mixture after 90 minutes were: 2,2-diphenyl-1-picrylhydrazine (2, 45% yield), 2-(4-hydroxyphenyl)-2-phenyl-1-picrylhydrazine (3, 12% yield), and 2-(4-nitrophenyl)-2-phenyl-1-picrylhydrazine (5, 18% yield). In Figure 1 one can observe how the visible absorption spectrum changed during the reaction: the DPPH peaks with λ max 328 and 520 nm decreased, and new bands appeared due to the formation of reaction products 2 (316 nm), 17 We checked that UV irradiation of 8a or 8b in benzene generates HO…”
Section: Introductionmentioning
confidence: 99%